Temporomandibular Joint Bone Tissue Resorption in Patients with Early Rheumatoid Arthritis Can Be Predicted by Joint Crepitus and Plasma Glutamate Level - Anna-Kari Hajati; Karin Näsström; Per Alstergren; Johan Bratt; Sigvard Kopp (Mediators of Inflammation)
The aim was to investigate whether bone tissue resorption in early RA is related to crepitus of the temporomandibular joint (TMJ) and systemic levels of inflammatory mediators and markers and sex steroid hormones. Twentynine women and 18 men with recently diagnosed RA were examined for TMJ bone erosions with computerized tomography and TMJ crepitus was assessed. Blood samples were analyzed for glutamate, 5-HT, TNF, IL-1β, IL-6, VEGF, inflammatory markers, and estradiol, progesterone and testosterone. The TMJ erosion score was positively correlated to glutamate, and TMJ crepitus where crepitus, glutamate and ESR explained 40% of the variation in the bone erosion score. In the patients without crepitus, bone erosion score was positively correlated to glutamate, which was not the case in the patients with crepitus. In conclusion, the results of this study show that TMJ bone tissue resorption can be predicted by TMJ crepitus and glutamate in early RA.